2021
DOI: 10.1021/acs.chemmater.1c01420
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Order and Disorder in Double Four-Membered Rings via Raman Spectroscopy during Crystallization of LTA Zeolite

Abstract: Fluoride (F–) has been essential for the synthesis of low-defect siliceous zeolites. It has been hypothesized that F– balances the positive charges from organic structure-directing agents (OSDAs) and stabilizes key building units during zeolite crystallization such as the double four-membered ring (D4R). However, due to the lack of characterization techniques for investigating medium-range structures, including rings and cages formed during zeolite crystallization, the roles of F– in stabilizing building units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…As displayed in Figure 3 and Table 2, for the sample without TMA, no Q 3 peak was found in the 29 Si MAS NMR spectrum, implying a defect-free LTA structure with all positive charge from BULKY balanced by F − , consistent with our previous study. 20 With increasing TMA, the ratio of Q 3 /(Q 3 + Q 4 ) grows accordingly, consistent with an increasing amount of anionic framework defects to balance charge. From the NMR data in Figure 3, we computed the Si−O − and SiOH distributions, which show a positive correlation between Si−O − and TMA + (Table S2).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…As displayed in Figure 3 and Table 2, for the sample without TMA, no Q 3 peak was found in the 29 Si MAS NMR spectrum, implying a defect-free LTA structure with all positive charge from BULKY balanced by F − , consistent with our previous study. 20 With increasing TMA, the ratio of Q 3 /(Q 3 + Q 4 ) grows accordingly, consistent with an increasing amount of anionic framework defects to balance charge. From the NMR data in Figure 3, we computed the Si−O − and SiOH distributions, which show a positive correlation between Si−O − and TMA + (Table S2).…”
Section: Resultsmentioning
confidence: 71%
“…Our previous computational and experimental study found negligible effects on the Raman spectra from these very low Al contents. 20 For this reason, we denote the resulting materials as Si-LTA. As reflected by XRD results (Figure 2a), all of the four siliceous LTA samples are fully crystalline with the characteristic diffraction peaks from the LTA framework.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeolites, which have uniform sub-nanometer-sized pore channels, tunable composition, acidic properties, and tailorable morphology, are widely used in the chemical industry as selective catalysts, adsorbents, and membranes. Among them, ZSM-5 zeolite (MFI-type framework), which has two intersecting 10-membered ring channels has attracted much attention of researchers. Its micropores have the dimensions in the range of 0.5–0.6 nm and the interconnected cavities on the framework (Figure S1) are useful for the synthesis of valuable chemical intermediates. However, a significant drawback in the zeolite catalyst is that the very presence of the micropores also brings diffusion limitation.…”
Section: Introductionmentioning
confidence: 99%